2016
DOI: 10.1152/ajpcell.00104.2015
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and SGK1 reduce the function of Na+/monocarboxylate transporter 1 (SMCT1/SLC5A8)

Abstract: SMCTs move several important fuel molecules that are involved in lipid, carbohydrate, and amino acid metabolism, but their regulation has been poorly studied. Insulin controls the translocation of several solutes that are involved in energetic cellular metabolism, including glucose. We studied the effect of insulin on the function of human SMCT1 expressed in Xenopus oocytes. The addition of insulin reduced α-keto-isocaproate (KIC)-dependent Na uptake by 29%. Consistent with this result, the coinjection of SMCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
2
3
0
Order By: Relevance
“…Although SMCT 1 and 2 transport a wide variety of substrates in various tissues, few studies have explored the regulatory mechanism for SMCT 1 and 2 expression. Previously, TNF‐α and insulin treatment were reported to suppress SMCT1 expression in in vitro experiments . In this study, we observed that SMCT 1 and 2 expression increased in a low glucose condition or after inhibition of cellular glucose uptake by SGLT2i, pointing to an association with attenuated intracellular ER stress .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Although SMCT 1 and 2 transport a wide variety of substrates in various tissues, few studies have explored the regulatory mechanism for SMCT 1 and 2 expression. Previously, TNF‐α and insulin treatment were reported to suppress SMCT1 expression in in vitro experiments . In this study, we observed that SMCT 1 and 2 expression increased in a low glucose condition or after inhibition of cellular glucose uptake by SGLT2i, pointing to an association with attenuated intracellular ER stress .…”
Section: Discussionsupporting
confidence: 56%
“…Previously, TNF-α and insulin treatment were reported to suppress SMCT1 expression in in vitro experiments. 58,59 In this study, we observed that SMCT 1 and 2 expression increased in a low glucose condition or after inhibition of cellular glucose uptake by SGLT2i, pointing to an association with attenuated intracellular ER stress. 44,45 Furthermore, the ER stress inhibitor PBA upregulated SMCT expression in renal proximal tubular cells, supporting the hypothesis of ER as a possible determinant of renal expression.…”
Section: Discussionsupporting
confidence: 49%
“…Both AKT (Berwick et al, 2004) and SGK1 (Seebohm et al, 2007) appear to be able to phosphorylate and activate PIKFYVE, thus regulating the localization and activity of diverse transporters, including the K + channel complex KCNQ1/KCNE1 (Seebohm et al, 2007), the Na + /monocarboxylate transporter SLC5A1 (Shojaiefard, Strutz-Seebohm, Tavare, Seebohm, & Lang, 2007), the creatine transporter SLC6A8 (Lopez-Barradas et al, 2016), the Ca 2+ -permeable cation channel TRPV6 (Sopjani et al, 2010), as well as the amino acid transporters EAAT2, -3, -4 (Gehring et al, 2009). In all these cases, experimental validation of the relative role and relevance of AKT and SGK1 is still lacking.…”
Section: Akt and Sgk1: Target Overlap And Selectivitymentioning
confidence: 99%
“…This suggests a possible role of SMCT1 in urate reabsorption in the kidney [167]. Another quite recent work showed the expression of both SMCT1 and SMCT2 in pancreas and also that SMCT1 function can be regulated by insulin [101].…”
Section: Slc5a8/smct1 and Slc5a12/smct2mentioning
confidence: 84%